Hubungan komitmen afektif dengan iklim organisasi dimediasi oleh organizational citizenship behaviour pada karyawan - Vitavela Ilmawati (Universitas Muhammadiyah Malang, 2021)
Organizational environment can affect organizational productivity. The interaction of employees with the organizational environment is referred to as organizational climate. Organizational climate is influenced by affective commitment and organizational citizenship behaviors. The purpose of this study was to determine the relationship between affective commitment and organizational climate mediated by organizational citizenship behaviors. Research subjects 174 staff. Data retrieval using random sampling technique and the method of Mediating Multiple Regression analysis. Collecting data using the Clior Scale to measure the organizational climate variable, the OCQ Scale to measure the affective commitment variable and the OCB Scale to measure the organizational citizenship behavior variable. The results show that organizational citizenship behaviors can mediate the relationship between affective commitment and organizational climate. This study shows that affectively committed employees can reduce negative aspects in the company so that they will show OCB behavior by complying with all company regulations and maintaining good relations with all members of the organization then it can create a positive organizational climate for the company.